Implementasi Kebijakan Pendidikan Murah Berkualitas Sesuai Perda Kota Semarang Nomor 1 Tahun 2007 tentang Penyelenggaraan Pendidikan (Studi Kasus di SMP Negeri 27 Semarang) - Melati Putri; Hesti Lestari; Slamet Santoso (Journal of Public Policy and Management Review, 2014)
Qualified Affordable Education Policy is a policy made by the local government of Semarang city to alleviate student is unable to prevent dropouts and improve the quality of education . The government made some efforts to achieve policy objectives . Efforts are made comprised of BOS funding, budget provision of providing education, adequacy of teachers according to their respective fields, the scholarship application are less capable, the liberation of all costs for poor students , teacher certification and others. In the implementation of low- quality implementation of education policy there are several factors that affect implementation .This study aims to describe the implementation of low- quality education policies undertaken by the local government of Semarang city and to describe the factors that influence policy implementation . This research uses descriptive qualitative method . Data collection method used is in-depth interviews and documentation techniques .The results of this study are the low quality of education policy implementation in 27 Junior High School of Semarang there are still things that make it optimal implementation of the policy . It is seen from the precision and accuracy of the policies that have not run optimally . Factors that affect the implementation , such as communication , resources , and bureaucratic structures are also not going well.